Results of Implementation of Supplemental Instruction Programs for Student-Athletes at the University of Richmond - Ivey, George N.; Traynelis-Yurek, Elaine (My University, 1985)
University of Richmond does not have developmental courses at all and no priority registration for athletes. Incoming freshmenn athletes were tested for deficiencies and course placement. Certain scores indicated students should be placed in classes which had supplemental instruction. Results comparing Fall 1983 to Fall 1984 for freshman football athletes showed an increase in GPA, decrease in academic probation, increase in semester hours passed, and no failures in SI courses.
Keywords: models; legislation; academic performance; academic predictors